Fiber material with high moisture permeability and cooling effect and method for producing the same

CN122899005APending Publication Date: 2026-10-13WUHAN TEXTILE UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610940320.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-26
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

这种方式不仅未解决层间结合不牢与性能衰减问题,还可能阻碍水分传输

Benefits of technology

1)本发明的技术方案通过润湿性与孔径的协同设计,构建了明确且稳定的水分定向传输路径。亲水层(接触角<90°)能迅速捕获皮肤表面的液态汗液;导流层(接触角居中)作为过渡,降低了亲水层与疏水层(接触角>90°)之间的界面能垒,引导水分顺畅通过;疏水层(接触角>90°)则对水分形成“推动”效应,防止其回渗,并因其最大的平均孔径,有效降低了水分向外蒸发的阻力。这种从内到外“亲水-疏水”的化学梯度与“小孔-大孔”的物理梯度相结合,不仅显著提升了水分由内层向外层的定向传输效率与稳定性,还从根本上克服了传统后整理或填料添加法中因材料脱落或分布不均导致的性能衰减问题,确保了单向导湿效果的长期可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122899005A_ABST
    Figure CN122899005A_ABST
Patent Text Reader

Abstract

The application provides a fiber material with high moisture permeability and cooling effect and a preparation method thereof, and belongs to the field of nanofibers. The fiber material with high moisture permeability and cooling effect comprises a hydrophilic layer, a flow guide layer, a hydrophobic layer and a radiation heat dissipation layer which are sequentially stacked in the thickness direction. The hydrophilic layer comprises first fibers, the flow guide layer comprises second fibers, the hydrophobic layer comprises third fibers, and the radiation heat dissipation layer comprises fourth fibers. The static water contact angle of the first fibers is less than 90 degrees, the static water contact angle of the third fibers is greater than 90 degrees, and the static water contact angle of the second fibers is between the static water contact angles of the first fibers and the third fibers. The average pore diameter of the hydrophilic layer, the flow guide layer and the hydrophobic layer increases in the direction from the hydrophilic layer to the hydrophobic layer. The fourth fibers have a porous structure. The technical scheme of the application can realize excellent and stable one-way moisture conductivity and rapid cooling effect, so as to meet the increasing demand of people for high-performance functional clothing materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanofiber technology, specifically to a fiber material with high moisture permeability and cooling effect, and its preparation method. Background Technology

[0002] One-way moisture-wicking materials utilize the difference in wettability to drive directional moisture transport by constructing a hydrophilic layer on the inside and a hydrophobic layer on the outside, and are widely used in clothing and medical fields. However, existing technologies mostly rely on finishing processes or heterogeneous composites to achieve the wetting gradient, and their functional layers are prone to detachment or uneven distribution due to friction and washing, resulting in insufficient durability of uniway moisture-wicking performance. In terms of human body cooling, radiative heat dissipation technology radiates heat to the external environment through high infrared emitting materials. Currently, a common method is to add fillers such as ceramic particles to the fibers, but this also faces problems such as easy filler detachment and unstable heat dissipation performance.

[0003] Existing technologies that combine unidirectional moisture wicking and radiative heat dissipation are mostly simple superpositions, such as coating the surface of moisture-wicking fabric with a heat-dissipating coating. This approach not only fails to solve the problems of weak interlayer bonding and performance degradation, but may also hinder moisture transfer.

[0004] Therefore, there is an urgent need to develop a new type of material that is structurally stable and highly efficient in unidirectional moisture conduction and cooling. Summary of the Invention

[0005] In view of the technical problems existing in the background art, the purpose of this invention is to provide a fiber material with high moisture permeability and cooling effect, and a method for preparing the same. This fiber material with high moisture permeability and cooling effect can achieve excellent and stable one-way moisture wicking properties and rapid cooling effect, thereby meeting the growing demand for high-performance functional clothing materials.

[0006] To achieve the above objectives, this invention proposes a fiber material with high moisture permeability and cooling properties, comprising: A hydrophilic layer, a flow-guiding layer, a hydrophobic layer, and a radiative heat dissipation layer are sequentially stacked along the thickness direction; The hydrophilic layer comprises a first fiber, the flux-guiding layer comprises a second fiber, the hydrophobic layer comprises a third fiber, and the radiative heat dissipation layer comprises a fourth fiber; wherein... The static water contact angle of the first fiber is less than 90°, the static water contact angle of the third fiber is greater than 90°, and the static water contact angle of the second fiber is between that of the first fiber and the third fiber. The average pore size of the hydrophilic layer, the flow-conducting layer, and the hydrophobic layer increases sequentially from the hydrophilic layer to the hydrophobic layer. The fourth fiber has a porous structure.

[0007] As a further improvement of the present invention, the average pore size of the hydrophilic layer, the flow guiding layer and the hydrophobic layer increases in a gradient from the hydrophilic layer to the hydrophobic layer.

[0008] As a further improvement of the present invention, the average pore size of the hydrophilic layer is 30nm-300nm; and / or, The average pore size of the flow-guiding layer is 400 nm-1000 nm; and / or, The average pore size of the hydrophobic layer is 500nm-1500nm.

[0009] As a further improvement of the present invention, the static water contact angle of the first fiber is 35°-85°; The static water contact angle of the second fiber is 50°-125°; The static water contact angle of the third fiber is 95°-130°.

[0010] As a further improvement of the present invention, the porosity of the radiative heat dissipation layer is 70%-95%.

[0011] As a further improvement of the present invention, the diameter of the first fiber is 40nm-500nm; The diameter of the second fiber is 40nm-600nm; The diameter of the third fiber is 40nm-750nm; The diameter of the fourth fiber is 0.4μm-2.5μm.

[0012] To achieve the above objectives, the present invention also proposes a method for preparing a fiber material with high moisture permeability and cooling properties, comprising: The raw material of the first fiber is dissolved in the first solvent to prepare the first spinning solution, and a hydrophilic layer is deposited on the receiving device by electrospinning. The raw material of the second fiber is dissolved in the second solvent to prepare the second spinning solution, and a flow-guiding layer is formed by electrospinning on the surface of the hydrophilic layer. The raw material of the third fiber is dissolved in the third solvent to prepare the third spinning solution, and a hydrophobic layer is deposited on the surface of the guide layer by electrospinning. The raw materials of the fourth fiber are dissolved in the fourth solvent to prepare the fourth spinning solution. The radiative heat dissipation layer is deposited on the surface of the hydrophobic layer by electrospinning, resulting in a fiber material with high moisture permeability and cooling effect.

[0013] As a further improvement of the present invention, the raw material of the first fiber includes hydrophilic nylon; and / or, The raw materials for the third fiber include hydrophobic nylon; and / or, The raw materials for the fourth fiber include polyoxymethylene.

[0014] As a further improvement of the present invention, the raw materials for the second fiber include hydrophilic nylon and hydrophobic nylon.

[0015] As a further improvement of the present invention, the voltage for electrospinning is (+16kV) - (+26kV), and the voltage of the receiving device is (-5kV) - 0; and / or, The distance between the spinning needle and the collecting device in electrospinning is 10cm-18cm; and / or, The inner diameter of the spinning needle in electrospinning is 0.4 mm-0.7 mm; and / or, In the first spinning solution, the mass fraction of the raw material for the first fiber is 15wt%-25wt%; and / or, In the second spinning solution, the mass fraction of the raw material for the second fiber is 15wt%-25wt%; and / or, In the third spinning solution, the mass fraction of the raw material for the third fiber is 15wt%-25wt%; and / or, In the fourth spinning solution, the mass fraction of the raw material for the fourth fiber is 5wt%-10wt%.

[0016] The beneficial effects of this invention are: 1) The technical solution of this invention constructs a clear and stable directional moisture transport path through the synergistic design of wettability and pore size. The hydrophilic layer (contact angle <90°) can quickly capture liquid sweat on the skin surface; the guiding layer (central contact angle) acts as a transition, reducing the interfacial energy barrier between the hydrophilic layer and the hydrophobic layer (contact angle >90°), guiding moisture to pass smoothly; the hydrophobic layer (contact angle >90°) has a "pushing" effect on moisture, preventing its backflow, and due to its largest average pore size, it effectively reduces the resistance to moisture evaporation. This combination of the "hydrophilic-hydrophobic" chemical gradient from the inside to the outside and the "micropore-macropore" physical gradient not only significantly improves the efficiency and stability of directional moisture transport from the inner layer to the outer layer, but also fundamentally overcomes the performance degradation problem caused by material shedding or uneven distribution in traditional finishing or filler addition methods, ensuring the long-term reliability of the unidirectional moisture-wicking effect.

[0017] 2) The technical solution of this invention significantly improves the radiative heat dissipation performance of fiber materials with high moisture permeability and cooling effect through the fourth fiber with a porous structure on the radiative heat dissipation layer. The porous structure greatly increases the specific surface area and infrared emissivity of the material. After human body heat (mainly radiated in the mid-infrared band) is conducted to this layer, it can efficiently dissipate this heat to the external low-temperature environment (such as the sky) in the form of infrared radiation, thereby achieving active cooling without energy consumption. This mechanism complements the unidirectional moisture-wicking evaporative cooling, together forming a rapid and lasting cooling effect.

[0018] 3) Furthermore, the three-dimensional network formed by the porous fourth fiber produces strong Mie and Rayleigh scattering in the solar spectrum (especially visible and near-infrared light). Light is repeatedly scattered between countless fiber and pore interfaces, making it extremely difficult to penetrate, thus achieving an ultra-high solar reflectivity.

[0019] 4) The porous fourth fiber is filled with air and is an excellent thermal insulator. It can effectively isolate the object being cooled below from the heat conduction and convection between the object and the ambient air, prevent external heat backflow, and thus significantly improve the net cooling effect.

[0020] In summary, this invention utilizes a hydrophilic layer to efficiently capture moisture, a flow-guiding layer to smoothly transfer and divert moisture, a hydrophobic layer to achieve unidirectional barrier and accelerate evaporation, and a radiative heat dissipation layer to provide additional active heat dissipation channels. This multi-level, multi-mechanism synergy not only solves the problems of unstable moisture absorption and wicking performance and limited functionality in traditional materials, but also avoids reliance on complex post-processing or expensive functional fillers. Thus, while achieving excellent performance, it meets the needs of large-scale industrial production of high-performance functional textiles.

[0021] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, specific embodiments of this application are given below. Attached Figure Description

[0022] To more clearly illustrate the technical solutions of this application, the accompanying drawings used in this application will be briefly described below. Obviously, the drawings described below are merely some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without any creative effort.

[0023] Figure 1 This is a scanning electron microscope image of the hydrophilic layer prepared in Example 1; Figure 2 This is a statistical diagram of the diameter of the first fiber in the hydrophilic layer prepared in Example 1; Figure 3 The first fiber of the hydrophilic layer prepared in Example 1 has a water contact angle with water. Figure 4 This is a scanning electron microscope image of the flow-guiding layer prepared in Example 1; Figure 5 This is a statistical diagram of the second fiber diameter of the flow guiding layer prepared in Example 1; Figure 6 The water contact angle of the second fiber of the guide layer prepared in Example 1; Figure 7This is a scanning electron microscope image of the hydrophobic layer prepared in Example 1; Figure 8 This is a statistical diagram of the third fiber diameter of the hydrophobic layer prepared in Example 1; Figure 9 The third fiber of the hydrophobic layer prepared in Example 1 has a water contact angle with the water. Figure 10 This is a scanning electron microscope image of the radiation heat dissipation layer prepared in Example 1; Figure 11 This is a statistical diagram of the fourth fiber diameter of the radiative heat dissipation layer prepared in Example 1; Figure 12 The fourth fiber of the radiative heat dissipation layer prepared in Example 1 has a water contact angle. Figure 13 This is a graph showing the solar reflectivity. Figure 14 This is a graph showing the emissivity of the mid-infrared spectrum. Detailed Implementation

[0024] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.

[0026] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.

[0027] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0028] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.

[0029] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).

[0030] In the description of the embodiments of this application, the technical terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the embodiments of this application and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application.

[0031] In the description of the embodiments of this application, unless otherwise expressly specified and limited, technical terms such as "installation," "connection," "joining," and "fixing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in the embodiments of this application can be understood according to the specific circumstances.

[0032] One-way moisture-wicking materials utilize the difference in wettability to drive directional moisture transport by constructing a hydrophilic layer on the inside and a hydrophobic layer on the outside, and are widely used in clothing and medical fields. However, existing technologies mostly rely on finishing processes or heterogeneous composites to achieve the wetting gradient, and their functional layers are prone to detachment or uneven distribution due to friction and washing, resulting in insufficient durability of uniway moisture-wicking performance. In terms of human body cooling, radiative heat dissipation technology radiates heat to the external environment through high infrared emitting materials. Currently, a common method is to add fillers such as ceramic particles to the fibers, but this also faces problems such as easy filler detachment and unstable heat dissipation performance.

[0033] Existing technologies that combine unidirectional moisture wicking and radiative heat dissipation are mostly simple superpositions, such as coating the surface of moisture-wicking fabric with a heat-dissipating coating. This approach not only fails to solve the problems of weak interlayer bonding and performance degradation, but may also hinder moisture transfer.

[0034] Therefore, there is an urgent need to develop a novel material with stable structure and high efficiency in unidirectional moisture permeability and cooling. To achieve the above objective, this invention proposes a fiber material with high moisture permeability and cooling properties, comprising: A hydrophilic layer, a flow-guiding layer, a hydrophobic layer, and a radiative heat dissipation layer are sequentially stacked along the thickness direction; The hydrophilic layer comprises a first fiber, the flux-guiding layer comprises a second fiber, the hydrophobic layer comprises a third fiber, and the radiative heat dissipation layer comprises a fourth fiber; wherein... The static water contact angle of the first fiber is less than 90°, the static water contact angle of the third fiber is greater than 90°, and the static water contact angle of the second fiber is between that of the first fiber and the third fiber. The average pore size of the hydrophilic layer, the flow-conducting layer, and the hydrophobic layer increases sequentially from the hydrophilic layer to the hydrophobic layer. The fourth fiber has a porous structure.

[0035] The technical solution of this invention constructs a clear and stable directional moisture transport path through the synergistic design of wettability and pore size. The hydrophilic layer (contact angle <90°) rapidly captures liquid sweat from the skin surface; the guiding layer (central contact angle) acts as a transition, lowering the interfacial energy barrier between the hydrophilic and hydrophobic layers (contact angle >90°), guiding moisture smoothly through; the hydrophobic layer (contact angle >90°) creates a "pushing" effect on moisture, preventing backflow, and due to its largest average pore size, effectively reduces the resistance to moisture evaporation. This combination of an internal-to-external "hydrophilic-hydrophobic" chemical gradient and a "micropore-macropore" physical gradient not only significantly improves the efficiency and stability of directional moisture transport from the inner to the outer layer, but also fundamentally overcomes the performance degradation problems caused by material shedding or uneven distribution in traditional finishing or filler addition methods, ensuring the long-term reliability of the unidirectional moisture-wicking effect. The fourth fiber with a porous structure on the radiative heat dissipation layer significantly enhances the radiative heat dissipation performance of the fiber material with high moisture permeability and cooling effect. The porous structure significantly increases the material's specific surface area and infrared emissivity. When heat from the human body (primarily radiated in the mid-infrared band) is conducted to this layer, it efficiently dissipates this heat into the external low-temperature environment (such as the sky) via infrared radiation, thus achieving active cooling without consuming energy. This mechanism, combined with unidirectional hygroscopic evaporative cooling, results in a rapid and sustained cooling effect.

[0036] As a further improvement of the present invention, the average pore size of the hydrophilic layer, the flow guiding layer and the hydrophobic layer increases in a gradient from the hydrophilic layer to the hydrophobic layer.

[0037] In this embodiment, by designing the average pore size of the hydrophilic layer, the channeling layer, and the hydrophobic layer to increase in a gradient from the hydrophilic layer to the hydrophobic layer, the transport dynamics and efficiency of moisture between each layer can be further optimized. Specifically, the hydrophilic layer has the smallest average pore size, which allows it to more quickly adsorb and lock in trace amounts of sweat on the skin surface through capillary action while possessing strong hydrophilicity, forming the initial moisture-absorbing driving force. The channeling layer has a larger average pore size than the hydrophilic layer, which can both receive moisture from the hydrophilic layer and avoid weakening the transport dynamics due to excessive pore size. On the contrary, the moderate increase in pore size reduces the frictional resistance of moisture flow within the layer, ensuring that moisture migrates uniformly and continuously to the hydrophobic layer. The hydrophobic layer has the largest average pore size. This larger pore structure provides a smoother channel for moisture to be transported from the channeling layer to the surface of the hydrophobic layer. On the other hand, when moisture reaches the surface of the hydrophobic layer, it can accelerate the heat exchange between the moisture and the external environment, causing the sweat to evaporate quickly into a gaseous state and diffuse into the air. In summary, this gradient design of pore size matches the wettability gradient of each fiber layer, enabling the transport of moisture within the highly permeable and cooling fiber material to exhibit a highly efficient synergistic state of "adsorption-conduction-evaporation," further enhancing the overall unidirectional moisture-wicking effect.

[0038] As a further improvement of the present invention, the average pore size of the hydrophilic layer is 30nm-300nm.

[0039] In this embodiment, the average pore size of the hydrophilic layer is limited to the range of 30nm-300nm. The hydrophilic layer can provide sufficient capillary adsorption sites through its rich microporous structure, ensuring rapid capture of sweat on the skin surface.

[0040] As a further improvement of the present invention, the average pore size of the flow guide layer is 400nm-1000nm.

[0041] In this embodiment, the average pore size of the flow-guiding layer is limited to the range of 400nm-1000nm, so that water transported from the hydrophilic layer through capillary action can smoothly enter the flow-guiding layer; at the same time, the flow-guiding layer itself can still maintain a certain capillary driving force to continuously and stably push water towards the hydrophobic layer.

[0042] As a further improvement of the present invention, the average pore size of the hydrophobic layer is 500nm-1500nm.

[0043] In this embodiment, the average pore size of the hydrophobic layer is limited to the range of 500nm-1500nm, providing a more unobstructed macroscopic channel for the transport of water from the conductive layer to the surface of the hydrophobic layer. When water reaches the hydrophobic layer, the larger pore size allows the surface of the hydrophobic layer to hold more liquid water and form a thinner water film, thereby increasing the contact area between water and the outside air and accelerating the evaporation rate.

[0044] As a further improvement of the present invention, the static water contact angle of the first fiber is 35°-85°.

[0045] In this embodiment, the static water contact angle of the first fiber is limited to the range of 35°-85°. This range of hydrophilicity ensures that the hydrophilic layer has a strong affinity for sweat seeping from the skin surface. When sweat comes into contact with the surface of the hydrophilic layer, due to the high-energy state of the fiber surface, it spreads rapidly and is adsorbed by the microporous structure between the fibers through capillary effect, forming a good initial moisture absorption effect and preventing sweat from accumulating at the interface between the skin and the hydrophilic layer, thus avoiding a sticky feeling.

[0046] As a further improvement of the present invention, the static water contact angle of the second fiber is 50°-125°.

[0047] In this embodiment, the static water contact angle of the second fiber is limited to the range of 50°-125°, which lies between the static water contact angles of the first fiber in the hydrophilic layer and the third fiber in the hydrophobic layer, forming a wettability gradient transition from hydrophilic to hydrophobic. This transition design effectively reduces the interfacial energy barrier when water is transported from the highly hydrophilic first fiber to the highly hydrophobic third fiber. Specifically, when water enters the flow-guiding layer from the hydrophilic layer, because the hydrophilicity of the second fiber is weaker than that of the first fiber but stronger than that of the third fiber, the adhesion of water to the surface of the second fiber is moderate. It will not be excessively retained due to excessive hydrophilicity, nor will it be difficult to spread and transport due to excessive hydrophobicity. This just-right wettability allows water to form a continuous liquid film or flow within the flow-guiding layer, and with the help of capillary forces, it migrates smoothly towards the hydrophobic layer, ensuring the continuity and efficiency of the entire unidirectional moisture-guiding process and avoiding the phenomenon of "blockage" or "backflow" of water at the interlayer interface.

[0048] As a further improvement of the present invention, the static water contact angle of the third fiber is 95°-130°.

[0049] In this embodiment, the static water contact angle of the third fiber is limited to the range of 95°-130°. This range of hydrophobicity allows the hydrophobic layer to significantly repel moisture transported to its surface. When moisture migrates from the conductive layer to the hydrophobic layer, due to the low surface energy of the third fiber surface, the moisture is difficult to spread on its surface and tends to form spherical droplets. On the one hand, this effectively prevents moisture already transported to the outer layer from back to the inner layer due to changes in external pressure or humidity, thus ensuring the "one-way" effect of unidirectional moisture wicking. On the other hand, the small contact area between the spherical droplets and the surface of the hydrophobic layer makes it easier for them to detach from the surface of the hydrophobic layer or quickly evaporate into a gaseous state under the combined action of gravity and evaporation driving force, further accelerating the sweat excretion efficiency and ensuring the dryness of the outer layer of the fiber material with high moisture permeability and cooling effect.

[0050] As a further improvement of the present invention, the porosity of the fourth fiber is 70%-95%.

[0051] In this embodiment, the porosity of the fourth fiber is limited to the range of 70%-95%, which significantly improves the performance of the radiative heat dissipation layer. Higher porosity means that a large number of interconnected micropores are formed within the radiative heat dissipation layer. These micropores not only reduce the overall density of the material and increase the air content, thereby reducing heat transfer within the layer via thermal conduction and providing a certain degree of thermal insulation (preventing the transfer of external high temperatures to the skin), but more importantly, the abundant micropore structure greatly increases the contact area between the fourth fiber and the external environment. This allows the material to more effectively receive heat transferred from the human body via thermal conduction and emit it back to the low-temperature environment as mid-infrared radiation. Simultaneously, these micropore structures also help capture and scatter some infrared radiation from the environment, reducing the material's absorption of heat from the environment.

[0052] As a further improvement of the present invention, the diameter of the first fiber is 40nm-500nm.

[0053] In this embodiment, the diameter of the first fiber is limited to the range of 40nm-500nm. This diameter range is chosen primarily to enhance the capillary adsorption capacity of the hydrophilic layer and the overall structural softness. A finer fiber diameter allows the hydrophilic layer to form a denser fiber network structure, with smaller and more uniformly distributed micropores between the fibers. According to the capillary effect principle, smaller pore sizes generate stronger capillary attraction, thereby significantly enhancing the hydrophilic layer's ability to rapidly adsorb and lock in trace amounts of sweat from the skin surface, ensuring that sweat is effectively captured in its early stages. Simultaneously, the fine diameter of the first fiber also imparts a soft touch and a close fit to the body to the hydrophilic layer. When this highly breathable and cooling fiber material is applied to clothing and other close-fitting applications, it can improve wearing comfort. Furthermore, a smaller fiber diameter also helps increase the specific surface area of ​​the hydrophilic layer, further improving its contact efficiency with sweat and its moisture absorption rate.

[0054] As a further improvement of the present invention, the diameter of the second fiber is 40nm-600nm.

[0055] In this embodiment, the diameter of the second fiber is limited to the range of 40nm-600nm. The network structure formed by the second fiber within this diameter range ensures that water can migrate directionally from the hydrophilic layer to the hydrophobic layer with high efficiency under the synergistic effect of capillary driving force and wettability gradient, thereby ensuring the high efficiency and stability of the entire flow conduction process.

[0056] As a further improvement of the present invention, the diameter of the third fiber is 40nm-750nm.

[0057] In this embodiment, the diameter of the third fiber is limited to the range of 40nm-750nm. The network structure of the third fiber within this diameter range can ensure the air permeability of the hydrophobic layer, and through the appropriate gaps between the fibers, it can work together with the hydrophobic surface properties to ensure the realization of the "pushing" effect on moisture and the anti-backflow function, thereby maintaining the unidirectional moisture-wicking efficiency of the entire fiber material with high moisture permeability and cooling effect.

[0058] As a further improvement of the present invention, the diameter of the fourth fiber is 0.4μm-2.5μm.

[0059] In this embodiment, the diameter of the fourth fiber is limited to the range of 0.4μm-2.5μm. The porous network constructed by the fourth fiber within this diameter range has a more reasonable size and distribution of micropores, which can provide sufficient surface sites for mid-infrared radiation emission while ensuring air circulation in the pores. Thus, while improving infrared emissivity, it also takes into account the material's air permeability and structural stability, enabling the radiative heat dissipation effect to be performed efficiently and persistently.

[0060] To achieve the above objectives, the present invention also proposes a method for preparing a fiber material with high moisture permeability and cooling properties, comprising: The raw material of the first fiber is dissolved in the first solvent to prepare the first spinning solution, and a hydrophilic layer is deposited on the receiving device by electrospinning. The raw material of the second fiber is dissolved in the second solvent to prepare the second spinning solution, and a flow-guiding layer is formed by electrospinning on the surface of the hydrophilic layer. The raw material of the third fiber is dissolved in the third solvent to prepare the third spinning solution, and a hydrophobic layer is deposited on the surface of the guide layer by electrospinning. The raw materials of the fourth fiber are dissolved in the fourth solvent to prepare the fourth spinning solution. The radiative heat dissipation layer is deposited on the surface of the hydrophobic layer by electrospinning, resulting in a fiber material with high moisture permeability and cooling effect.

[0061] In this embodiment, a layer-by-layer electrospinning method is used to precisely control the composition, structure, and thickness of each functional layer, ensuring a tight and stable interfacial bond between the hydrophilic layer, the flow-guiding layer, the hydrophobic layer, and the radiative heat dissipation layer, thus avoiding interlayer delamination. Specifically, during the preparation of the hydrophilic layer, by adjusting the concentration and viscosity of the first spinning solution and the electrospinning process parameters (such as spinning voltage, receiving distance, and feed rate), the diameter and arrangement of the first fibers, as well as the average pore size of the hydrophilic layer, can be precisely controlled to meet the static water contact angle and pore size range requirements mentioned above, thereby endowing the hydrophilic layer with excellent hygroscopic properties. Subsequently, electrospinning of the second spinning solution is carried out directly on the surface of the hydrophilic layer to form the flow-guiding layer. During this process, the composition and spinning parameters of the second spinning solution are independently adjusted according to the design requirements of the flow-guiding layer to ensure that the static water contact angle and average pore size of the second fiber are between those of the hydrophilic and hydrophobic layers. Similarly, the hydrophobic layer and the radiative heat dissipation layer are also prepared independently using a similar electrospinning process. The spinning solution formulation and process parameters are optimized separately for the characteristics of the third and fourth fibers, ultimately forming a fiber material with a clear hierarchical structure and synergistic functions, exhibiting high moisture permeability and cooling properties. This setup not only ensures the independence and precision of each layer's function but also facilitates synergistic effects between layers, achieving an optimal match between the unidirectional moisture conduction and radiative heat dissipation performance of the fiber material with high moisture permeability and cooling properties. Furthermore, electrospinning technology itself has advantages such as ease of operation, relatively low cost, and the ability for large-scale continuous production. Fibers spun using electrospinning technology have the advantages of small diameter and large specific surface area, resulting in faster moisture absorption and conduction rates based on their structure.

[0062] As a further improvement of the present invention, the raw material of the first fiber includes hydrophilic nylon.

[0063] In this embodiment, hydrophilic nylon was chosen as the raw material for the first fiber based on its excellent hydrophilicity, good mechanical properties, and biocompatibility. The hydrophilic nylon molecular chain contains a large number of polar amide groups (-CONH-), which can form strong hydrogen bonds with water molecules, thus endowing the first fiber with excellent hydrophilic properties and ensuring efficient adsorption of sweat from the skin by the hydrophilic layer. Simultaneously, nylon itself has high strength and abrasion resistance. After being electrospun into nanofibers, it ensures that the hydrophilic layer is not prone to fiber breakage or structural damage during long-term use and repeated washing, maintaining its original microporous structure and capillary adsorption capacity, and avoiding a decrease in unidirectional moisture wicking effect due to insufficient material mechanical properties. Furthermore, hydrophilic nylon has good biocompatibility and is unlikely to cause allergic or irritating reactions when in contact with human skin. This is crucial for applications that directly contact the skin (such as clothing fabrics and medical dressings), improving the comfort and safety of the product.

[0064] As a further improvement of the present invention, the raw material for the third fiber includes hydrophobic nylon.

[0065] In this embodiment, hydrophobic nylon was chosen as the raw material for the third fiber because of its excellent hydrophobicity, mechanical properties similar to hydrophilic nylon, and good chemical stability after hydrophobic modification. Hydrophobic nylon is typically modified by introducing long-chain alkyl or fluorocarbon groups into the nylon molecular chain, or by plasma treatment or coating the fiber surface. In the modified hydrophobic nylon molecular chain, hydrophobic groups are enriched on the material surface, significantly reducing the surface energy of the fiber and ensuring effective water repulsion and anti-backflow function of the hydrophobic layer. Simultaneously, hydrophobic nylon retains the inherent high strength and toughness of nylon materials, making its fiber network structure less prone to damage when subjected to tensile, frictional, or other external forces. This maintains a stable pore structure and hydrophobicity, ensuring the performance stability of the hydrophobic layer after long-term use. Furthermore, hydrophobic nylon exhibits good chemical resistance and washability. In daily use, it is less prone to chemical changes that could cause hydrophobicity loss when exposed to sweat, detergents, and other substances. This ensures that the unidirectional moisture-wicking effect of the highly breathable and cooling fiber material can withstand repeated washing and long-term use. When used in conjunction with hydrophilic nylon, it also ensures good compatibility between the hydrophobic and hydrophilic layers and the flow-guiding layer at the interface, reducing the risk of interlayer delamination due to significant differences in material properties and further enhancing the overall structural stability of the highly breathable and cooling fiber material.

[0066] As a further improvement of the present invention, the raw material of the fourth fiber includes polyoxymethylene.

[0067] In this embodiment, polyoxymethylene (POM) was chosen as the raw material for the fourth fiber because of its unique molecular structure, which endows it with excellent infrared radiation performance, good mechanical strength, and chemical stability. The POM molecular chain is composed of repeating -O-CH2- units. This highly symmetrical and polar molecular structure gives it a high infrared emissivity in the mid-infrared band. When heat from the human skin surface is transferred to the radiative heat dissipation layer through thermal conduction, the POM fibers can efficiently emit this heat back to the external environment in the form of mid-infrared radiation, thus achieving a passive cooling effect. Simultaneously, POM is a highly crystalline polymer with excellent rigidity, hardness, and wear resistance. After being electrospun into nanofibers, the radiative heat dissipation layer can maintain good structural integrity and dimensional stability while maintaining high porosity, making it less prone to deformation or damage from external forces, ensuring that its radiative heat dissipation performance does not diminish during long-term use. In addition, polyoxymethylene (POM) possesses excellent chemical resistance and weather resistance, exhibiting good resistance to water, organic solvents, and common sweat components (such as salt), and is not prone to degradation or performance changes, ensuring the stability and reliability of the radiant heat dissipation layer in complex operating environments. It also boasts good processing performance and the advantage of inexpensive raw materials.

[0068] As a further improvement of the present invention, the raw materials for the second fiber include hydrophilic nylon and hydrophobic nylon.

[0069] In this embodiment, a blend of hydrophilic and hydrophobic nylon is selected as the raw material for the second fiber to precisely control the static water contact angle of the second fiber by adjusting the ratio of the two raw materials, thereby achieving a smooth transition of wettability between the hydrophilic and hydrophobic layers. Specifically, hydrophilic nylon provides basic hydrophilicity, while hydrophobic nylon reduces overall hydrophilicity by introducing hydrophobic segments or groups. By optimizing the mixing ratio of the two, the surface energy of the second fiber can be made to fall between that of the first and third fibers, meeting the design requirements of the wettability gradient. Compared with single-component fiber modification, this method of selecting blended raw materials offers greater flexibility and stability in regulation. It allows for precise control of the hydrophilicity and hydrophobicity of the second fiber by simply adjusting the raw material ratio, ensuring that the flow-guiding layer plays a crucial "bridging" role in the unidirectional moisture-guiding process, promoting the efficient migration of water from the hydrophilic layer to the hydrophobic layer. Meanwhile, hydrophilic nylon and hydrophobic nylon share similar chemical structures (both are polyamide polymers), exhibiting good compatibility. During blending and spinning, phase separation is less likely to occur, resulting in a uniformly structured second fiber. This ensures the continuity and stability of the fiber network and pore structure within the flow-guiding layer, avoiding problems such as uneven fiber performance or decreased interlayer bonding due to poor raw material compatibility. Furthermore, this blend system also considers the mechanical properties of the second fiber. Through proper proportioning, the flow-guiding layer possesses both sufficient flexibility to adapt to the deformation requirements of the overall membrane material and adequate strength to maintain its structural integrity, ensuring the long-term stability of the flow-guiding function of the fiber material with high moisture permeability and cooling properties during use.

[0070] As a further improvement of the present invention, the first solvent, the second solvent, and the third solvent are formic acid.

[0071] In this embodiment, formic acid was chosen as the first, second, and third solvents primarily because of its excellent solubility and good spinning adaptability for nylon raw materials (including hydrophilic nylon, hydrophobic nylon, and blends thereof). Formic acid is a highly polar organic solvent that can effectively disrupt the hydrogen bond interactions between nylon molecular chains, allowing the nylon macromolecular chains to fully expand and dissolve, forming a uniform and stable spinning solution. Specifically, for hydrophilic and hydrophobic nylon, formic acid can penetrate into the polymer interior, reducing intermolecular forces, thereby obtaining a solution with good spinnability at a suitable concentration. Its dissolution process is relatively mild, unlikely to cause degradation or cross-linking of nylon molecular chains, ensuring the mechanical properties of the spun fibers. Furthermore, formic acid has a low boiling point and appropriate volatility. During electrospinning, while the spinning solution stream is stretched and refined under a high-voltage electric field, the formic acid can rapidly evaporate, causing the fibers to solidify quickly and reducing fiber adhesion on the receiving device, which is beneficial for forming nanofibers with regular structure and uniform diameter.

[0072] As a further improvement of the present invention, the fourth solvent is 1,1,1,3,3,3-hexafluoro-2-propanol.

[0073] In this embodiment, 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) was selected as the fourth solvent due to its excellent solubility for polyoxymethylene (POM) and its suitable performance in the electrospinning process. POM, as a highly crystalline polymer, has poor solubility in conventional organic solvents. HFIP, as a strongly polar fluorinated solvent, with its unique molecular structure, can form a strong interaction with the POM molecular chains, effectively disrupting the crystalline structure of POM and dissolving it to form a stable and homogeneous fourth spinning solution. This lays a crucial foundation for the subsequent preparation of a radiative heat dissipation layer with a specific porous structure via electrospinning. Furthermore, as a commonly used biocompatible solvent, the residual amount of HFIP after spinning is easily controlled and removed, ensuring the biosafety of the final prepared fiber material with high moisture permeability and cooling properties, making it particularly suitable for applications that may come into contact with human skin. Its efficient dissolution of POM and good adaptability to the spinning process ensure that the fourth fiber can be successfully spun and form a porous network structure with excellent radiative heat dissipation performance.

[0074] As a further improvement of the present invention, the voltage of electrospinning is (+16kV)-(+26kV), and the voltage of the receiving device is (-5kV)-0.

[0075] In this embodiment, setting the electrospinning voltage within the positive range of (+16kV) to (+26kV) and the receiving device voltage within the negative range of (-5kV) to 0 or ground helps improve the stability of the spinning process, optimize fiber morphology, and increase deposition efficiency. This voltage combination can establish an electrostatic field of suitable strength between the spinning nozzle and the receiving device. When the positive voltage is +16kV or higher, this voltage is sufficient to overcome the surface tension and viscous resistance of the spinning solution, causing the spinning solution to form a stable Taylor cone at the nozzle tip and eject a continuous jet. Controlling the upper limit of the positive voltage at +26kV can avoid excessive jet splitting, unstable flight trajectory, or even defects such as fiber beads and splashing caused by excessive voltage, thereby ensuring the uniformity of the diameter and the integrity of the morphology of the prepared fibers. For the receiving device, a negative terminal of (-5kV)-0 or a grounded setting is used. On the one hand, this enhances the attraction to the positively charged jet, improves the jet's directionality and deposition efficiency, and allows the fibers to accumulate more orderly on the receiving device. On the other hand, a suitable negative voltage (such as around -5kV) helps neutralize the repulsive force generated by charge accumulation during the jet's flight, reducing excessive diffusion and disordered entanglement of the fibers before deposition, thereby controlling the surface morphology and internal structural density of the fiber material. In the actual preparation of different functional layers, the voltage range can be fine-tuned according to the characteristics (viscosity, conductivity, etc.) of each spinning solution (such as the first to fourth spinning solutions). By precisely controlling this voltage parameter range, the high-quality molding of each nanofiber layer can be effectively guaranteed, thus ensuring that the hydrophilic layer, the conductive layer, the hydrophobic layer, and the radiative heat dissipation layer all meet the designed structural and performance requirements.

[0076] As a further improvement of the present invention, the distance between the spinning needle of the electrospinning and the spinning collection device is 10cm-18cm.

[0077] In this embodiment, the spinning distance between the electrospinning needle and the collecting device is set to 10cm-18cm. Controlling the spinning distance within this range provides sufficient solvent evaporation time for the jet, ensuring good fiber morphology, jet stability, and uniform fiber deposition. This also allows for the regulation of the structure of each functional layer, laying the foundation for achieving the designed functions of each layer. Furthermore, it is worth noting that in actual operation, the spinning distance can be fine-tuned according to requirements such as the solvent volatility, viscosity, and target fiber diameter of the spinning solution. For example, the spinning distance can be increased for spinning solutions with poor solvent volatility or high viscosity, and shortened for spinning solutions with high solvent volatility.

[0078] As a further improvement of the present invention, the inner diameter of the spinning needle in electrospinning is 0.4 mm to 0.7 mm.

[0079] In this embodiment, the spinning needle size for electrospinning is set within the range of 0.4 mm to suit the fluidity of the spinning solution, jet stability, and the diameter control requirements of the prepared fibers. When the viscosity of the spinning solution is in the medium range, this needle inner diameter ensures that the spinning solution is smoothly extruded from the needle under the propulsion rate. Specifically, for spinning solutions with relatively high viscosity, using a 0.4 mm needle reduces flow resistance and ensures stable liquid supply; while for spinning solutions with relatively low viscosity, using a 0.7 mm needle helps to prolong the residence time of the spinning solution at the needle tip, promotes the stable formation of the Taylor cone, and assists in adjusting the fineness of the final fiber by appropriately reducing the initial jet diameter. In addition, this needle size is readily available on the market and has good compatibility with common electrospinning propulsion systems (such as micro-injection pumps), facilitating experimental operation and replacement and maintenance in industrial production. In summary, by selecting spinning needles within this range, the diameter and morphology of each fiber layer can be more precisely controlled by adjusting parameters such as spinning voltage and spinning distance, providing a reliable process for constructing hydrophilic, conductive, hydrophobic, and radiative heat dissipation layers with specific structures and functions.

[0080] As a further improvement of the present invention, in the first spinning solution, the mass fraction of the raw material of the first fiber is 15wt%-25wt%.

[0081] In this embodiment, the mass fraction of the raw material of the first fiber in the first spinning solution is set to 15wt%-25wt% in order to precisely control the concentration and viscosity of the first spinning solution, thereby affecting the formation of the fiber and the microstructure of the hydrophilic layer during electrospinning.

[0082] As a further improvement of the present invention, in the second spinning solution, the mass fraction of the raw material of the second fiber is 15wt%-25wt%.

[0083] In this embodiment, the mass fraction of the raw material of the second fiber in the second spinning solution is set to 15wt%-25wt% in order to precisely control the concentration and viscosity of the second spinning solution, thereby affecting the formation of the fiber and the microstructure of the hydrophilic layer during electrospinning.

[0084] As a further improvement of the present invention, in the third spinning solution, the mass fraction of the raw material of the third fiber is 15wt%-25wt%.

[0085] In this embodiment, the mass fraction of the raw material of the third fiber in the third spinning solution is set to 15wt%-25wt% in order to precisely control the concentration and viscosity of the third spinning solution, thereby affecting the formation of fibers and the microstructure of the hydrophilic layer during electrospinning.

[0086] As a further improvement of the present invention, in the fourth spinning solution, the mass fraction of the raw material of the fourth fiber is 5wt%-10wt%.

[0087] In this embodiment, the mass fraction of the raw material of the fourth fiber in the fourth spinning solution is set to 5wt%-10wt% in order to precisely control the concentration and viscosity of the fourth spinning solution, thereby affecting the formation of fibers and the microstructure of the hydrophilic layer during electrospinning.

[0088] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0089] I. Preparation Method It should be noted that the hydrophilic nylon used in the following examples is the highly hydrophilic polyamide 6 prepared in Chinese Patent Publication No. CN114031771A, and the hydrophobic nylon used in the following examples is the toughened low water absorption nylon 6 in Chinese Patent Publication No. CN115073746A.

[0090] Example 1 A certain mass of hydrophilic nylon was dissolved in formic acid and completely dissolved under stirring at room temperature to prepare a 15wt% first spinning solution. The solution was then spun using electrospinning to form a hydrophilic layer. During electrospinning, a 20mL syringe equipped with an electrospinning needle with an inner diameter of 0.41mm was used. The solution injection rate was 0.03mm / min, the roller collector rotation speed was 100r / min, and the spinning distance from the spinning needle to the roller collector was 15cm. The electrospinning voltage was +22kV and -2kV.

[0091] Hydrophilic nylon and hydrophobic nylon in a mass ratio of 2:3 were dissolved in formic acid and completely dissolved under stirring at room temperature to prepare a 20wt% second spinning solution. A conductive layer was then deposited on the surface of the hydrophilic layer using electrospinning. During electrospinning, a 20mL syringe equipped with an electrospinning needle with an inner diameter of 0.7mm was used. The solution injection rate was 0.03mm / min, the roller collector rotation speed was 100r / min, and the spinning distance from the spinning needle to the roller collector was 10cm. The electrospinning voltage was +25kV and -5kV.

[0092] A certain mass of hydrophobic nylon was dissolved in formic acid and completely dissolved under stirring at room temperature to prepare a 20wt% third spinning solution. The solution was then deposited on the surface of the conductive layer using electrospinning to form a hydrophobic layer. During electrospinning, a 20mL syringe equipped with an electrospinning needle with an inner diameter of 0.7mm was used. The solution injection rate was 0.03mm / min, the roller collector rotation speed was 100r / min, and the spinning distance from the spinning needle to the roller collector was 10cm. The electrospinning voltage was +26kV and -5kV.

[0093] A certain mass of POM (polyoxymethylene) powder (commercial grade, Aladdin) was mixed with 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP, 99%, Aladdin), and then stirred at 60°C for 1 hour until the solution was uniform and transparent, preparing a 5wt% fourth spinning solution. A radiative heat dissipation layer was then deposited on the hydrophobic surface using electrospinning, thus obtaining the fiber material of Example 1 with high moisture permeability and cooling properties. During the electrospinning process, a 10mL syringe equipped with an electrospinning needle with an inner diameter of 0.6mm was used. The solution injection rate was 0.333mm / min, the roller collector rotation speed was 100r / min, the spinning distance from the spinning needle to the roller collector was 18cm, and the electrospinning voltage was +16kV.

[0094] Example 2 A certain mass of hydrophilic nylon was dissolved in formic acid and completely dissolved under stirring at room temperature to prepare a 20wt% first spinning solution. The solution was then spun using electrospinning to form a hydrophilic layer. During electrospinning, a 20mL syringe equipped with an electrospinning needle with an inner diameter of 0.41mm was used. The solution injection rate was 0.03mm / min, the roller collector rotation speed was 100r / min, and the spinning distance from the spinning needle to the roller collector was 15cm. The electrospinning voltage was +22kV and -2kV.

[0095] Hydrophilic nylon and hydrophobic nylon in a mass ratio of 2:3 were dissolved in formic acid and completely dissolved under stirring at room temperature to prepare a 20wt% second spinning solution. A conductive layer was then deposited on the surface of the hydrophilic layer using electrospinning. During electrospinning, a 20mL syringe equipped with an electrospinning needle with an inner diameter of 0.7mm was used. The solution injection rate was 0.03mm / min, the roller collector rotation speed was 100r / min, and the spinning distance from the spinning needle to the roller collector was 10cm. The electrospinning voltage was +25kV and -5kV.

[0096] A certain mass of hydrophobic nylon was dissolved in formic acid and completely dissolved under stirring at room temperature to prepare a 20wt% third spinning solution. The solution was then deposited on the surface of the conductive layer using electrospinning to form a hydrophobic layer. During electrospinning, a 20mL syringe equipped with an electrospinning needle with an inner diameter of 0.7mm was used. The solution injection rate was 0.03mm / min, the roller collector rotation speed was 100r / min, and the spinning distance from the spinning needle to the roller collector was 10cm. The electrospinning voltage was +26kV and -5kV.

[0097] A certain mass of POM powder was mixed with 1,1,1,3,3,3-hexafluoro-2-propanol, and then stirred at 60°C for 1 hour until the solution was uniform and transparent, preparing a 5wt% fourth spinning solution. A radiative heat dissipation layer was then deposited on the surface of the hydrophobic layer using electrospinning, thus obtaining the fiber material of Example 2 with high moisture permeability and cooling properties. During the electrospinning process, a 10mL syringe equipped with an electrospinning needle with an inner diameter of 0.6mm was used. The solution injection rate was 0.333mm / min, the roller collector rotation speed was 100r / min, the spinning distance from the spinning needle to the roller collector was 18cm, and the electrospinning voltage was +16kV.

[0098] Example 3 The difference from Example 1 is that, in the first spinning solution, the mass fraction of the raw material of the first fiber is 15 wt%; in the second spinning solution, the mass fraction of the raw material of the second fiber is 15 wt%; in the third spinning solution, the mass fraction of the raw material of the third fiber is 20 wt%; and in the fourth spinning solution, the mass fraction of the raw material of the fourth fiber is 5 wt%. The remaining steps are roughly the same and will not be described in detail here, resulting in the fiber material of Example 3 with high moisture permeability and cooling effect.

[0099] Example 4 The difference from Example 1 is that, in the first spinning solution, the mass fraction of the raw material for the first fiber is 15 wt%; in the second spinning solution, the mass fraction of the raw material for the second fiber is 20 wt%; in the third spinning solution, the mass fraction of the raw material for the third fiber is 25 wt%; and in the fourth spinning solution, the mass fraction of the raw material for the fourth fiber is 5 wt%. The remaining steps are largely the same and will not be elaborated further here, resulting in the fiber material of Example 4 with high moisture permeability and cooling effect.

[0100] Example 5 The difference from Example 1 is that, in the first spinning solution, the mass fraction of the raw material of the first fiber is 15 wt%; in the second spinning solution, the mass fraction of the raw material of the second fiber is 20 wt%; in the third spinning solution, the mass fraction of the raw material of the third fiber is 20 wt%; and in the fourth spinning solution, the mass fraction of the raw material of the fourth fiber is 10 wt%. The remaining steps are roughly the same and will not be described in detail here, resulting in the fiber material of Example 5 with high moisture permeability and cooling effect.

[0101] Comparative Example 1 The difference from Example 1 is that no hydrophilic layer is provided. The remaining steps are roughly the same and will not be described in detail here. The fiber material of Comparative Example 1 is obtained.

[0102] Comparative Example 2 The difference from Example 1 is that no flow guide layer is set. The rest of the steps are roughly the same and will not be described in detail here, thus obtaining the fiber material of Comparative Example 2.

[0103] Comparative Example 3 The difference from Example 1 is that no hydrophobic layer is provided. The remaining steps are roughly the same and will not be described in detail here, resulting in the fiber material of Comparative Example 3.

[0104] Comparative Example 4 The difference from Example 1 is that no radiative heat dissipation layer is provided. The remaining steps are roughly the same and will not be described in detail here, resulting in the fiber material of Comparative Example 4.

[0105] II. Testing Methods Contact angle test: Cut several square samples with a size of 3cm×3cm, and use a droplet shape analyzer to measure the static water contact angle of the samples. Set the size of the water droplet squeezed out each time to 5μL, and repeat the test three times for each sample at room temperature to maintain accuracy.

[0106] Droplet diffusion test: A certain mass of brilliant blue hydrophilic dye was dissolved in an appropriate amount of deionized water to prepare a hydrophilic dye solution. Two 3cm × 3cm samples were cut from fiber materials with high moisture permeability and cooling properties. 5μL of the hydrophilic dye solution was dropped onto the center of the hydrophilic side of the sample, and the diffusion of the dye solution in the fiber materials with high moisture permeability and cooling properties was observed, and the diffusion diameter was measured.

[0107] Temperature change test: The surface temperature of the highly breathable and cooling fiber material covering sweaty skin was tested using a thermal infrared imager (FLUKETi400).

[0108] III. Analysis of Test Results for Each Embodiment and Comparative Example Table 1. Test results of Examples 1-5 and Comparative Examples 1-4 Table 1 shows that when the spinning solution concentration of the first fiber increases, the diameter of the first fiber increases, making it difficult for moisture to spread and diffuse within the fiber, resulting in a smaller diffusion diameter. This slightly reduces the water-conducting effect of the hydrophilic layer, leading to an increase in the surface temperature of the fiber material with high moisture permeability and cooling properties. When the mass fraction of the raw material of the second fiber increases, the diameter of the second fiber increases, making it difficult for moisture to spread, diffuse, and transport within the fiber, resulting in a smaller diffusion diameter. This also leads to an increase in the surface temperature of the fiber material with high moisture permeability and cooling properties. When the mass fraction of the raw material of the third fiber increases, the fiber diameter of the hydrophobic layer increases, resulting in a looser fiber network. This allows moisture to more easily contact and adhere to the fiber surface, reducing spreading resistance and facilitating moisture transport. This increases the diffusion diameter and lowers the surface temperature of the membrane. When the mass fraction of the raw material of the fourth fiber increases, the fiber diameter of the heat dissipation layer increases. Since the fiber has hydrophobic properties, moisture is less likely to spread and diffuse within the fiber, resulting in a smaller diffusion diameter. Furthermore, due to the reduced specific surface area of ​​the heat dissipation layer fibers, the radiative cooling performance also slightly decreases, leading to an increase in the surface temperature of the composite fiber material with high moisture permeability and cooling properties.

[0109] The comparative results show that when the composite fiber material with high moisture permeability and cooling effect lacks a hydrophilic layer, it is not conducive to the absorption and diffusion of moisture, the diffusion diameter becomes smaller, which is not conducive to moisture conduction and cooling, and the surface temperature of the fiber material increases. When the composite fiber material with high moisture permeability and cooling effect lacks a flow-guiding layer, the diffusion diameter becomes smaller, which is not conducive to moisture conduction and cooling, and the surface temperature of the fiber material increases. When the composite fiber material with high moisture permeability and cooling effect lacks a hydrophobic layer, the diffusion diameter becomes smaller, which is not conducive to moisture conduction and cooling, and the surface temperature of the fiber material increases. When the composite fiber material with high moisture permeability and cooling effect lacks a heat dissipation layer, the diffusion diameter changes little, but the cooling effect deteriorates, and the surface temperature of the membrane increases.

[0110] Depend on Figure 1 and Figure 2 It is known that the first fiber is an ultrafine nanofiber with a diameter of 40nm-80nm. It is uniform in thickness, and the formed membrane has a small pore size, strong capillary tension, strong spontaneous water conduction ability, and the microporous network formed enhances the unidirectional moisture conduction ability. It has high porosity and helps to achieve air and moisture permeability.

[0111] Depend on Figure 3 This indicates that the static water contact angle of the first fiber is less than 90°, and it has an excellent ability to absorb sweat from the skin surface when used as an inner layer.

[0112] Depend on Figure 4 and Figure 5 This indicates that the second fiber has a diameter of 85nm-145nm and is of uniform thickness.

[0113] Depend on Figure 6This indicates that the static water contact angle of the second fiber is between that of the first fiber and the third fiber, which helps to conduct sweat from the hydrophilic layer to the hydrophobic outer layer, while also allowing the liquid to spread quickly and preventing backflow.

[0114] Depend on Figure 7 and Figure 8 This indicates that the third fiber has a diameter of 95nm-150nm and is of uniform thickness.

[0115] Depend on Figure 9 This indicates that the static water contact angle of the third fiber is greater than 90°, forming a wetting gradient with the inner layer, which enhances the unidirectional moisture conduction and prevents backflow.

[0116] Depend on Figure 10 and Figure 11 This indicates that the fourth fiber, with a diameter of 900nm-1700nm, has a loose and porous structure. Its high specific surface area effectively increases the area for emitting thermal radiation, helping to radiate heat more efficiently in the infrared form. The three-dimensional network formed by the porous structure and nanofibers produces strong Mie and Rayleigh scattering in the solar spectrum (especially visible and near-infrared light). Light is repeatedly scattered between countless fiber and pore interfaces, making it extremely difficult to penetrate, thus achieving an ultra-high solar reflectivity.

[0117] Depend on Figure 12 This indicates that the static water contact angle of the fourth fiber is greater than 90°, which can block the entry of external liquid water while forming a wetting gradient with the inner layer, thus enhancing the unidirectional moisture conduction and non-backflow effect.

[0118] Depend on Figure 13 This indicates that the composite fiber material, which has high moisture permeability and cooling effect, has a solar reflectivity of up to 93.5%, absorbs very little solar energy, isolates external heat sources, and avoids being heated by the sun.

[0119] Depend on Figure 14 This indicates that the ATW has an emissivity of 81.9% (8-13μm band), which enables it to efficiently radiate heat into the cold outer space and enhance its own heat dissipation.

[0120] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A fiber material with high moisture permeability and cooling properties, characterized in that, include: A hydrophilic layer, a flow-guiding layer, a hydrophobic layer, and a radiative heat dissipation layer are sequentially stacked along the thickness direction; The hydrophilic layer includes a first fiber, the flux-guiding layer includes a second fiber, the hydrophobic layer includes a third fiber, and the radiative heat dissipation layer includes a fourth fiber; wherein... The static water contact angle of the first fiber is less than 90°, the static water contact angle of the third fiber is greater than 90°, and the static water contact angle of the second fiber is between that of the first fiber and the third fiber. The average pore size of the hydrophilic layer, the flow-guiding layer, and the hydrophobic layer increases sequentially from the hydrophilic layer to the hydrophobic layer. The fourth fiber has a porous structure.

2. The fiber material with high moisture permeability and cooling effect according to claim 1, characterized in that, The average pore size of the hydrophilic layer, the flow-guiding layer, and the hydrophobic layer increases in a gradient from the hydrophilic layer to the hydrophobic layer.

3. The fiber material with high moisture permeability and cooling effect according to claim 2, characterized in that, The average pore size of the hydrophilic layer is 30nm-300nm; The average pore size of the flow guide layer is 400nm-1000nm; The average pore size of the hydrophobic layer is 500nm-1500nm.

4. The fiber material with high moisture permeability and cooling effect according to claim 1, characterized in that, The static water contact angle of the first fiber is 35°-85°; The static water contact angle of the second fiber is 50°-125°; The static water contact angle of the third fiber is 95°-130°.

5. The fiber material with high moisture permeability and cooling effect according to claim 1, characterized in that, The porosity of the radiative heat dissipation layer is 70%-95%.

6. The fiber material with high moisture permeability and cooling effect according to claim 1, characterized in that, The diameter of the first fiber is 40nm-500nm; The diameter of the second fiber is 40nm-600nm; The diameter of the third fiber is 40nm-750nm; The diameter of the fourth fiber is 400 nm to 2.5 μm.

7. A method for preparing a fiber material with high moisture permeability and cooling effect, characterized in that, include: The raw material of the first fiber is dissolved in the first solvent to prepare the first spinning solution, and a hydrophilic layer is deposited on the receiving device by electrospinning. The raw material of the second fiber is dissolved in the second solvent to prepare the second spinning solution, and the conductive layer is deposited on the surface of the hydrophilic layer by electrospinning. The raw material of the third fiber is dissolved in the third solvent to prepare the third spinning solution, and a hydrophobic layer is formed on the surface of the guide layer by electrospinning. The raw material of the fourth fiber is dissolved in the fourth solvent to prepare the fourth spinning solution. The radiative heat dissipation layer is formed by electrospinning on the surface of the hydrophobic layer, thereby obtaining the fiber material with high moisture permeability and cooling effect.

8. The method for preparing the fiber material with high moisture permeability and cooling effect according to claim 7, characterized in that, The raw material for the first fiber includes hydrophilic nylon; and / or, The raw material for the third fiber includes hydrophobic nylon; and / or, The raw material for the fourth fiber includes polyoxymethylene.

9. The method for preparing the fiber material with high moisture permeability and cooling effect according to claim 8, characterized in that, The raw materials for the second fiber include hydrophilic nylon and hydrophobic nylon.

10. The method for preparing the fiber material with high moisture permeability and cooling effect according to claim 7, characterized in that, The voltage for electrospinning is (+16kV) - (+26kV), and the voltage for the receiving device is (-5kV) - 0; and / or, The distance between the electrospinning needle and the collecting device is 10cm-18cm; and / or, The inner diameter of the spinning needle in the electrospinning process is 0.4 mm to 0.7 mm; and / or, In the first spinning solution, the mass fraction of the raw material for the first fiber is 15wt%-25wt%; and / or, In the second spinning solution, the mass fraction of the raw material for the second fiber is 15wt%-25wt%; and / or, In the third spinning solution, the mass fraction of the raw material for the third fiber is 15wt%-25wt%; and / or, In the fourth spinning solution, the mass fraction of the raw material for the fourth fiber is 5wt%-10wt%.

Citation Information

Patent Citations

  • Preparation method of high-hydrophilicity polyamide 6 and high-hydrophilicity polyamide 6 fiber

    CN114031771A

  • Toughened low-water-absorption nylon 6 and preparation method thereof

    CN115073746A